Pengaruh Kompetensi, Pengembangan Karir dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Dinas Koperasi dan UMKM Kabupaten Konawe Utara - Tambunan, Rince; Nur, Muh.; Kaswidah, Kaswidah; Basru Wawo, Andi (Green Publisher Indonesia, 2025)
This study aims to test and analyze the effect of competence, career development, and organizational commitment on employee performance at the Office of Cooperatives and MSMEs of North Konawe Regency. The sample in this study consisted of all employees at the Office of Cooperatives and MSMEs of North Konawe Regency totaling 33 people. This study uses multiple linear regression analysis. The results showed that: (1) Competence, career development, and organizational commitment have a positive and significant effect on employee performance at the Office of Cooperatives and MSMEs of North Konawe Regency. (2) Competence has a positive and significant effect on employee performance at the Office of Cooperatives and MSMEs of North Konawe Regency. (3) Career development has a positive and significant effect on employee performance at the Office of Cooperatives and MSMEs of North Konawe Regency. (4) Organizational commitment has a positive and significant effect on employee performance at the Office of Cooperatives and MSMEs of North Konawe Regency.